Blockchain based supply-chain finance service platform - Xiaofeng MA; Mingxiao DU; Wenbing YU; Yi WANG (大数据)
Blockchain has the characteristics of decentralization,stability,security,and non-modifiability.With the further improvement and application of the blockchain technology,it will be connected with the traditional industries such as finance,medical treatment and logistics.This will radically change the existing operation modes in some industries and restructure a value network.An application of blockchain in the field of supply-chain finance was tried,and a supplychain finance service platform based on the blockchain technology was constructed.The platform combines blockchain technology with other traditional systems,providing a more convenient way of financing for all parties in the supply-chain,improving the transparency,traceability and security of the supply-chain.